The Concept of Sadism in the Current Empirical Literature - Bulut, Tara (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
The present theoretical review examines contemporary empirical literature on sadism, the trait which is the newest addition to the group of subclinical ‘dark personalities’ – psychopathy, narcissism and Machiavellianism. Having been previously studied only in penal and clinical settings, in the form of sexual sadism or sadistic personality disorder, it was only recently accepted as a dimensional construct present in the general population. With that in mind, this paper gives a brief account of its historical background, as well as previous conceptualisations. More importantly, it covers the latest empirical research on sadism as a subclinical trait, its position within the Dark Tetrad, and studies on its personality and behavioural correlates. Finally, by encompassing the slowly growing field of sadism investigation, it tries to pinpoint important implications and recommendations for future research.